THE DEVELOPMENTAL TEACHING VOLLEYBALL FOR CHILDREN OF 9 TO 11 YEARS OF AGE (Fiep Bulletin - online, 2013)
This study investigated the development of the teaching experiment in the formative process of initiation to learning volleyball for six (6) student volunteers of both sexes aged 9-11 years of both sexes and program participants of sports initiation offered by the School of Physical Education and Physiotherapy of Goiás - ESEFFEGO. The theoretical reasons that the actions of the trial was through the Theory of Developmental Education Vasili V. Davidov seeking the formation of theoretical concepts and scientific about the object under study, from the appropriation of scientific knowledge produced by historical-cultural humanity and purposeful activity. The overall objective of this research was to observe regularities occurring in developing the teaching experiment in training young beginners volleyball, aspects of ownership and generalization of core concepts of the game of volleyball, with the development of teaching and learning in the context of teaching developmental. More specifically intended to verify and describe significant elements of formation of concepts, concepts of ownership and generalization of concepts by students, before the development of the proposed content for teaching volleyball. Data analysis showed that teaching the sport of volleyball can be developed by the assumptions of the theory of developmental teaching constituting a potentially formative process of reasoning capabilities of their own students. It was concluded that the place of the subjects (teachers and students), their motives and their culture are guiding elements of learning activities that can directly influence the results.
Keywords: Developmental Education; Learning; Volleyball.